ChemInform Abstract: Dinuclear Manganese, Iron, Chromium, and Cobalt Complexes Derived from Aroylhydrazone Ligands: Synthetic Strategies, Crystal Structures, and Magnetic Properties. Issue 7 (January 2016) - Mameri, Samir; Specklin, David; Welter, Richard
Abstract: Review: 86 refs.